Accountants' Perspectives on Essential Skills for Digital Accountants that Enhance the Operational Performance of Small and Medium-sized Enterprises in Bangkok and Vicinity - Thongkul, Teekhatat (Executive Journal, 2025)
This study examined accountants' perspectives on essential digital skills that enhance the operational performance of small and medium-sized enterprises (SMEs) in Bangkok and its surroundings. Data was collected from 330 full-time accountants using stratified random sampling. Multiple regression analysis revealed that digital communication (β = 0.582), data analytics (β = 0.300), and technological proficiency (β = 0.220) had significant positive relationships with perceived operational performance, while accounting knowledge showed a negative relationship (β = -0.137). The application of an ethical framework was statistically insignificant. These findings suggest that sole reliance on traditional skills is inadequate for accountants operating in the contemporary business environment. Therefore, developing digital expertise alongside traditional accounting competencies is critical for enhancing SME performance in the digital environment. This study contributes to accounting literature by providing empirical evidence of the perceived hierarchy of digital skills needed in contemporary accounting practice and offers practical insights for accounting education and professional development.